2009
DOI: 10.1111/j.1530-0277.2009.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Alcohol Consumption and Health‐Risk Behaviors Among High School Students in Thailand

Abstract: Alcohol consumption is a serious problem among adolescents in Thailand and is strongly associated with various health-risk behaviors. Effective age- and gender-specific interventions should be implemented to discourage underage drinking and associated adverse health and social consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
61
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 26 publications
12
61
2
1
Order By: Relevance
“…Data collection was conducted during a regular class period with permission given from the class teachers and took between 15-20 minutes to complete. The questionnaire was modified from the one used in the series of repeated national school surveys of alcohol consumption and other health-risk behaviors (Assanangkornchai et al, 2009). It contains five sections: socio-demographic characteristics, such as age, sex, living situation (alone, with family, or with friends), parents' income, and work status; school performance, as measured by grade point average (GPA; range 0-4.00); perception of peer and family drinking norms; student's mobility; student's access to alcohol; and frequency and pattern of alcohol consumption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection was conducted during a regular class period with permission given from the class teachers and took between 15-20 minutes to complete. The questionnaire was modified from the one used in the series of repeated national school surveys of alcohol consumption and other health-risk behaviors (Assanangkornchai et al, 2009). It contains five sections: socio-demographic characteristics, such as age, sex, living situation (alone, with family, or with friends), parents' income, and work status; school performance, as measured by grade point average (GPA; range 0-4.00); perception of peer and family drinking norms; student's mobility; student's access to alcohol; and frequency and pattern of alcohol consumption.…”
Section: Methodsmentioning
confidence: 99%
“…A national school survey in 2007 found that vocational students had the highest rate of alcohol consumption and tended to be involved more with frequent binge and intoxicated drinking than high-school students (Assanangkornchai, Pattanasattayawong, Samangsri, & Mukthong, 2007). Binge drinkers were significantly more likely to have drinking consequences (e.g., driving after drinking, nausea and vomiting, and having a hangover) than were non-binge drinkers (Assanangkornchai, Mukthong, & Intanont, 2009).…”
mentioning
confidence: 99%
“…If the score was ≥8, it indicated a hazardous drinker (8)(9)(10)(11)(12)(13)(14)(15) or harmful user (16)(17)(18)(19) or alcohol dependence (≥20).…”
Section: Instrumentsmentioning
confidence: 99%
“…The project was approved by the Ethics Committee for Research in Human Subjects of the Faculty of Medicine, Prince of Songkla University. Details of the survey methods were published elsewhere Assanangkornchai et al, 2009). …”
Section: Settingmentioning
confidence: 99%
“…A series of repeated surveys among high-school students in southern Thailand was initiated in 2002 and conducted annually for four years, with the aim of following the trends of alcohol and substance use and other health-risk behaviors among youth (Assanangkornchai, Pattanasattayawong, Samangsri, & Mukthong, 2007). In 2007 and 2009, it was expanded into a national school survey, which initially was meant to be carried out biannually to assess the country-wide impact of underage drinking and related prevention and control activities (Assanangkornchai, Mukthong, & Intanont, 2009). This study aims to examine the six-year trends and the factors associated with alcohol consumption over a 30-day period among high-school students between 2003 and 2009 in southern Thailand.…”
mentioning
confidence: 99%